Ground fuel characteristics of burnt peat in Raja Musa Forest Reserve, Selangor, Malaysia - Musa, Dayang Nur Sakinah (2016)
Peat swamp forest in Malaysia is an important ecosystem that acts as flood mitigation, climate change mitigation, and carbon storage. Nowadays, peat having an issues especially on fire. The study of burnt peat characteristics were still insufficient, thus, the study on burnt and unburnt peat in Raja Musa Forest Reserve (RMFR) were done. Additionally, the seasonal influence between dry and wet season also examined in this study, as well as the peat depth impacts on the RMFR peat. With these information, the fuel characteristic (physical, chemical, thermal ad burning properties) can be determined in comparison with the type of peat, seasonal affect and also influenced of peat depth in RMFR. Peat samples were collected in compartment 99 for burnt area, and compartment 1 for unburnt area. The peat samples of dry season from both areas were obtained in February, 2014, and the wet season in May, 2014.These samples were collected using an auger at four layers of peat, i.e., at the surface, and below ground of 0.5m, 1.0m and 1.5m depths. The physical properties includes bulk density, moisture content, and LOI which indicates the organic matter of peat. Bulk density indicates the compaction of the peat, the findings shows highest bulk density in burnt peat of dry season with 0.35 g/cm3 (at 1.0m), and lowest on the surface of unburnt peat during dry season with 0.27 g/cm3. The bulk density shows no significant differences among the depths, peat types, and seasons. The moisture content shows significant difference between peat types, wherein burnt peat was higher in moisture content compared to unburnt peat with 712.45% in burnt peat, and 498.16% in unburnt peat. Similar to moisture content, LOI shows Significantly different between burnt and unburnt peat, where burnt shows higher organic matter with 29.31 %, and lower in unburnt peat with 18.06%. Moreover, LOI shows significantly different amongst the depths of burnt peat where 1.5m depth shows the highest organic matter with 26.50%. For chemical properties, pH values indicates the acidity of the peat, and the results shows high significant difference between the season, wherein wet season (4.69) shows less acidic compared to dry season (4.19). Similarly to pH values, CEC shows significant difference between season, where wet seasons (106.39cmol/kg) higher in CEC and lower in dry season (49.14 cmol/kg). CEC also shows significantly different between peat types, where unburnt shows higher CEC with 89.87 cmollkg, and lower in burnt peat with 65.65 cmol/kg. The total carbon content in RMFR shows significant difference amongst the depths in burnt peat where it increasing down the depth with 31.77% (surface), 42.61% (0.5m), 45.06% (1.0m), 47.32% (1.5m). Besides, the total N content shows significant difference between peats types, wherein unburnt peat (1.33%) higher in N content compared to bumt peat (1.02%). The total N content also shows significantly difference amongst the depth, where it reducing down the depth with 1.62 (surface), 1.26 (O.5m), 1.23 (1.0m), and 1.21 (1.5m). Total P content shows significantly difference between burnt and unburnt peat, where the burnt peat (0.06%) was higher in total P content compared to unburnt peat (0.03%). Moreover, total P content shows significantly different amongst the depths in burnt and unburnt peat, where it reducing down the depth. Burnt peat shows 0.11% (Surface), 0.05% (0.5m), 0.04% (1.0m), and 0.04% (1.5m); unburnt peat shows 0.05% (Surface), 0.03% (0.5m), 0.03% (1.0m), 0.02% (1.5m). The extractable K amount shows highly significant difference between seasons and peat types, wherein dry season (142.39I-1g/g) was higher in K amount compared to wet season (80.02 I-Ig/g), and burnt peat (138.02 I-Ig/g) was higher than unburnt peat (84.39 I-Ig/g). Extractable K amount shows significantly different among the depths in unburnt peat where it reducing down the depths 204.46 1-19/g (surface), 50.71 1-19/g (0.5m), 45.99 1-19/g (1.Om), and 36.41 1-19/g (1.5m). Similar to K, the extractable Ca amount shows significantly higher in dry season (845.75 1-19/g), compared to wet season (106.41 1-19/g); and the Ca amount were significantly different, in where burnt peat were higher in Ca amount with 819.22 1-19/g, compared to unburnt peat with 132.94 I-Ig/g. The extractable Mg amount also shows significantly different between seasons, wherein dry season (263.41 I-Ig/g) was higher in Mg amount compared to wet season (56.20 I-Ig/g). Moreover, extractable amount of Na shows significant difference between peat types wherein, the unburnt peat were significantly higher in Na amount compared to burnt peat with 140.64 1-19/g and 55.92 1-19/g, respectively. For the thermal properties, TGA and DSC analyses for dry and wet season indicated that in burnt peat, surface peat was more thermally stabled compared to the 1.5m depth, however, in unburnt peat, the 1.5m depth. Burning properties shows significantly different of burning time between the peat types, wherein the unburnt peat (173.38 minutes) took longer time to completely turn into ashes compared to burnt peat (99.83 minutes). The burning time also shows Significantly different amongst the depths where, 130.33 minutes (surface), 171.83 minutes (O.5m), 201.50 minutes (1.0m), and 189.83 minutes (1.5m). In a conclusion, some of the characteristics were significantly influenced by the type of peat, the season and different layers of peat depth. For instance, the P content was higher in burnt peat than unburnt peat, the pH was less acidic during wet season than in dry season, and N content was higher at the surface and decreased down to below ground.